INFORMATION OPENNESS OF THE MUNICIPAL SYSTEM OF EDUCATION: THE EXPERIENCE OF SOCIAL AUDIT - Tatiana E. Zerchaninova; Olga V. Novgorodtseva (Образование и наука)
The aim of the investigation is to analyze information openness municipal education system, identify problems and develop practical recommendations in dealing with them. Methods. The conducted study is based on the methodology of the social audit, which includes the content analysis of the official websites of educational institutions in the network «Internet», the diagnosis of awareness among parents about the schools activities, expert assessment of informational openness of schools and the development of practical recommendations for improving information schools transparency. Research methods involve: description, analysis of documents, questionnaires, expert interviews, analysis of statistical data. Results. The article presents the results of a social audit of information openness of the municipal General educational system of Pervouralsk city district. The analysis of the content of the official websites of educational organizations in the network «Internet» was conducted at the first stage of social audit. It showed that only one school website fully complies with the proposed requirements. The best developed parameter of website is technological effectiveness; less developed – the communicativeness and multimedia. Diagnostics of awareness among parents of the pupils of the schools activities was conducted at the second stage of the social audit. A survey of parents has shown that the most popular are the traditional ways of obtaining information: teacher-parent meetings and communication with child. Less than half of parents receive information via the websites of the schools. Expert assessment of the information openness of schools was realized at the third stage. Practical recommendations on improvement of information openness of schools have been developed at the fourth stage. Scientific novelty. A new scientific idea of social audit of information openness municipal education system was set on the basis of the authors’ research that enriches the scientific concept of social audit. Authors have developed a new diagnostic technique that will reveal the state of information openness of municipal education system; proved promising use of social auditing techniques in the practice of evaluation of information openness of the municipal education system. Practical significance. The implications of the research findings prove that the authors of the given paper have developed and tested the diagnostic methods of the social audit of information openness of the municipal education system. The research results demonstrate the prospects of the practical use of the theory of social audit in practice; and the practical recommendations for further improvement of information openness of the municipal education system. The results of the study can be used in the activities of the Department of education Pervouralsk city district and other municipalities, as well as heads of educational organizations can use the investigation data to improve information openness of the municipal education system.